Weed Control with Postemergence Applications of Status, Armezon, Atrazine, Corvus, Verdict, and Roundup PowerMax in Irrigated Corn - R. Currie; P. Geier (Kansas Agricultural Experiment Station Research Reports, 2016)
All postemergence herbicides provided greater than 98% control of quinoa, common sunflower, Palmer amaranth, and green foxtail. Crabgrass and Russian thistle were more difficult to control. All postemergence herbicides except Roundup PowerMax (glyphosate) alone controlled Russian thistle and crabgrass greater than 89%. Diflexx (dicamba) plus Roundup PowerMax was slightly more efficacious on kochia than Status (diflufenzopyr + dicamba) plus Armezon (topramezone) with atrazine and Roundup PowerMax, and all other herbicides were intermediate for kochia control. Corn yields did not differ between herbicide treatments. However, all herbicides increased grain yields.
Keywords: irrigated corn; weed control; postemergence applications; kochia; quinoa; common sunflower; Palmer amaranth; green foxtail; Status; Dicamba; Diflufenzopyr; Armezon; Topramezone; Atrazine; Corvus; Isoxaflutole; Thiencarbazone; Verdict; Dimethenamid; Saflufenacil; Roundup PowerMax; glyphosate